Identifikasi Efek Protektif Berupa Antioksidan Terhadap Antioksidan - Shalsabila Jasmira Aisyah (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Garlic is a type of vegetable from Allium sativum L. Garlic has been used as an herbal medicine for thousands of years because of the active compounds in it. Active compounds as antioxidants contained in garliv play a very important role in preventing damage to cells and organs from the oxidation process caused by the increase in free radicals by cigarette smoke. Purpose: To identify the protective effect of grlic in the form of antioxidants against free radicals. Methods: Using literature studies from national and international research journals by summarizing the discussion topics and comparing the results presented in the articles. Results: Garlic has been widely studied as a natural antioxidant because it has an active organosulfur compound which has properties as a therapeutic ingredient in the form of antibacterial, antiviral, antifungal, antithrombotic, antibiotic, anticancer, antioxidant, immunomodulatory, anti-inflammatory, and hypoglycaemic effects. These organosulfur substances are in the form of flavonoids, adenosine, phone, and alliin. Allyl thiosulfate, which derived from alliin through the alliinase process, is responsible for reducing lipids, anticancer, and antioxidants. The results of various studies have shown that local single clove garlic contains more antioxidants than other types. Previous research has also shown that with the DPPH method, aged garlic with ethanol solvent has higher antioxidants than fresh garlic and with water solvents. Conclusion: Of the various kinds of garlic that exist, it has been proven that one that has more antioxidant properties is single clove garlic and aged garlic with ethanol than fresh garlic with allyl thiosulfate as its most active compound